Infant Temperament: Association with Maternal Depression Symptoms in Pregnancy and Postpartum - Garcia, Natália Vanzo [UNESP]; Padovani, Flávia Helena Pereira [UNESP]; Perosa, Gimol Benzaquen [UNESP] (FapUNIFESP (SciELO), 2022)
Research regarding the association between child temperament and maternal symptoms of depression remains inconclusive. This study aimed to compare the temperament of babies during their first year of life in relation to their mother's depression symptoms in pregnancy and/or postpartum. The study also identified risk factors for negative affectivity, extraversion, and effortful control. Fifty-four mother-infant dyads participated in the study, divided according to maternal depression symptoms into four groups: symptoms during pregnancy, postpartum, at both times, and without symptoms. The Edinburgh Postpartum Depression Scale and Infant Behavior Questionnaire were used. Children of mothers with depression symptoms had higher negative affectivity scores, activity levels, and lower effortful control scores. The prediction analysis revealed that negative affectivity and effortful control were explained by maternal postpartum depression symptoms, indicating that caring for the mother in her adaptation to motherhood can prevent impairment to infant temperament.
Temperamento Infantil: Associação com Sintomas Depressivos Maternos na Gestação e no Pós-Parto
Temperamento Infantil: Asociación con Síntomas Depresivos Maternos en el Embarazo y el Posparto
Keywords: childhood development; depression; personality; postpartum depression